The usability of construction and demolition wastes stabilized using alkali activated fly ash as filler material - Geckil, Tacettin; Sarici, Talha; Aksoy, Huseyin Suha (Pontificia Univ Catolica Chile, Escuela Construccion Civil, 2025)
Since construction and demolition waste (CDW) contain materials such as gypsum, wood, brick, plaster, etc., its engineering properties may not be at the desired quality. Therefore, if CDW is to be recycled and reused, the properties of CDW may need to be improved by various methods. In this study, the modifications in compaction and strength properties of CDW obtained from demolished building were investigated by adding fly ash (FA) at certain ratios. For this purpose, modified proctor, unconfined compression strength and California bearing ratio (CBR) tests were conducted on the CDW with and without FA-added. As a result of the experimental studies, it was observed that the addition of alkaline activator solution (AA) to the CDW increased the strength of the CDW. In addition, the strength of CDW increased significantly with the usage of AA in FA-added CDW samples. The FA additive ratio that gave the highest strength in the tests with water and AA was found to be 5% and 15%, respectively. As a result of the study, it is predicted that CDW with FA and AA can be used as a filling material as an alternative to natural aggregate.
Keywords: Construction and demolition waste; fly ash; soil improvement; geopolymer; filling